Investment Implications of Selected WTO Agreements and the Proposed Multilateral Agreementon Investment - Vocke, Matthias (IMF Working Papers; Working Paper ;, 1997)
The substantial increase in foreign direct investment (FDI) in recent years has triggered a discussion of a uniform treatment of investment in international law. Most contributions to the multilateral investment framework derive from the World Trade Organization (WTO) agreements on trade liberalization. The resulting framework is incomplete, as the WTO agreements restrict their focus on investment to aspects related to international trade and often apply to selected sectors only. A broader investment regime is needed to provide a more neutral incentive framework for investment liberalization and to promote efficient international investment flows.